MECHANISM FOR PREPARING THE REVENUE AND EXPENDITURE BUDGET OF DURUNG VILLAGE, MESJID RAYA DISTRICT, ACEH BESAR REGENCY - Badruzzaman; Aula, Nurul Jannatul; Armiwal (Dinasti International Journal of Digital Business Management, 2022)
Budget planning is a very important thing to be done by the government, both at the central, provincial and village levels. The Government Regulation on Villages has required villages/villages to prepare a Village Revenue and Expenditure Budget (APBG) in a participatory manner. APBG is determined annually by the Keuchik together with Tuha Peut. APBG is a manifestation of the face of the village government, because APBG was born from the combination of political processes and participation. APBG is said to be good if the allocation of spending is more for the needs of residents/community empowerment, especially those living below the poverty line. Conversely, APBG is said to be bad if there is a difference. The formulation of the problem in this study is How is the Mechanism of the Village Government in the Process of Preparing the Revenue and Expenditure Budget in Durung Village, Mejid Raya District, Aceh Besar Regency and What Obstacles Arise in Preparing the Revenue and Expenditure Budget in Durung Village, Mejid Raya District, Aceh Besar Regency and the purpose of this study is to Describe the Mechanism of Preparing the Revenue and Expenditure Budget in Durung Village, Mejid Raya District, Aceh Besar Regency and to Describe the obstacles that arise in the preparation of the Revenue and Expenditure Budget and its resolution in Durung Village, Mejid Raya District, Aceh Besar Regency, the method used in this study is a qualitative method that uses a descriptive approach.